A RETROSPECTIVE STUDY ON DRUG UTILIZATION PATTERN OF POISONING CASES ADMITTED IN A TERTIARY CARE TEACHING HOSPITAL - SASIDHARAN, PRASANAND (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Poisoning with suicidal intention is a serious health issue among adults. Poisoning, as an emergency, is more common in India due to the easy availability of poisons, increased use of chemicals in industrial and domestic purposes. The objective of the study is to evaluate the nature of poisoning cases and the drug utilization pattern of poisoning cases. Methods: A medical record-based retrospective data collection was conducted over a period of 21/2 years. Each prescription was analyzed by the demographic profile, the manner of poisoning (accidental or suicidal), the number of pharmacological agents causing poisoning, and type or name of the pharmacological agent responsible for the poisoning. Results: Among 127 total patients, 113 cases were suicidal. Systemic poisons (47.24%) were more consumed in our study, among which benzodiazepines (16.54%) being the most common sub-class ingested. Of the 862 medications prescribed, normal saline (38.97%) was the most commonly infused intravenous fluid. Gastric lavage (38.1%) has been the most frequently used general measures. Injection pantoprazole (50.6%) was the commonly prescribed anti-ulcer drug. The most commonly used analgesic (47.83%) was paracetamol, antimicrobial agent was cefotaxime (25%), Vitamin and minerals were Vitamin B complex (68%), steroid was hydrocortisone (76%), and antidote was atropine (37.5%). Conclusion: The magnitude of poisoning was high for suicidal purposes, in the young age group and in females. Intravenous fluids and general measures were the mainstay of the management of poisoned cases. Educational programs with an emphasis on preventive measures for toxic exposures are necessary to create awareness and to construct preventive strategies. Suggestions like poisoning centers in tertiary care hospitals will also help decrease morbidity and mortality.